Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13195-021-00805-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neurofilament light and phosphorylated tau 181 as biomarkers of Alzheimer’s disease pathology and clinical disease progression

Abstract: Background To assess the performance of plasma neurofilament light (NfL) and phosphorylated tau 181 (p-tau181) to inform about cerebral Alzheimer’s disease (AD) pathology and predict clinical progression in a memory clinic setting. Methods Plasma NfL and p-tau181, along with established cerebrospinal fluid (CSF) biomarkers of AD pathology, were measured in participants with normal cognition (CN) and memory clinic patients with cognitive impairment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 31 publications
(29 reference statements)
0
44
0
1
Order By: Relevance
“…This finding was subsequently verified by others ( Lewczuk et al, 2004 ; Fagan et al, 2011 ; Tang et al, 2014 ) and later also was confirmed with the measurement of serum ptau181 ( Shekhar et al, 2016 ). Recent studies demonstrated that blood ptau181 can predict cortical brain atrophy ( Llibre-Guerra et al, 2019 ; Tissot et al, 2021 ), tau and amyloid-beta pathology ( Lantero Rodriguez et al, 2020 ; Clark et al, 2021 ; Moscoso et al, 2021b ), differentiate AD from other neurodegenerative diseases ( Mielke et al, 2018 ; Thijssen et al, 2020 ; Grothe et al, 2021 ) and identify AD across the clinical continuum ( Janelidze et al, 2020a ; Karikari et al, 2020b , 2021 ). In familial AD, plasma ptau181 levels may rise as early as 16 years before clinical onset ( O’connor et al, 2020 ).…”
Section: Properties Of Neurofilaments Relevant To Their Use As Biomarkersmentioning
confidence: 99%
“…This finding was subsequently verified by others ( Lewczuk et al, 2004 ; Fagan et al, 2011 ; Tang et al, 2014 ) and later also was confirmed with the measurement of serum ptau181 ( Shekhar et al, 2016 ). Recent studies demonstrated that blood ptau181 can predict cortical brain atrophy ( Llibre-Guerra et al, 2019 ; Tissot et al, 2021 ), tau and amyloid-beta pathology ( Lantero Rodriguez et al, 2020 ; Clark et al, 2021 ; Moscoso et al, 2021b ), differentiate AD from other neurodegenerative diseases ( Mielke et al, 2018 ; Thijssen et al, 2020 ; Grothe et al, 2021 ) and identify AD across the clinical continuum ( Janelidze et al, 2020a ; Karikari et al, 2020b , 2021 ). In familial AD, plasma ptau181 levels may rise as early as 16 years before clinical onset ( O’connor et al, 2020 ).…”
Section: Properties Of Neurofilaments Relevant To Their Use As Biomarkersmentioning
confidence: 99%
“…Results from a very recent study seem to be in agreement with these findings as blood biomarkers of neuronal and glial degeneration were found to be elevated in hospitalized COVID-19 patients with new onset cognitive dysfunction (specifically, toxic-metabolic encephalopathy, TME) [ 269 ]. Specifically, they showed increased levels of total tau, neurofilament light chain (NfL), glial fibrillary acidic protein (GFAP), and ubiquitin carboxy-terminal hydrolase L1 (UCHL1) in the blood of neuro-COVID patients, which together indicated a profound neurological insult comparable to non-COVID patients with AD [ 269 , 270 ]. It is of great significance to note that these neurodegenerative biomarkers are also elevated after BBB disruption and were found to be associated with a higher risk of in-hospital death and reduced rates of discharge from hospital [ 269 ].…”
Section: Covid-19 and Neurodegenerationmentioning
confidence: 99%
“…According to this vision, peripheral biomarkers of neuroinflammation should be considered as true core markers of AD, accessible for implementing the diagnosis and the clinical follow-up of patients. Further studies with novel sensitive techniques (e.g., Simoa) comparing the central and peripheral compartments are therefore advisable, analogously to what has been recently made, for example, for phosphorylated tau [ 194 ].…”
Section: Discussionmentioning
confidence: 99%